2017
DOI: 10.1111/hsc.12498
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening community mental health competence-A realist informed case study from Dehradun, North India

Abstract: Few accounts exist of programmes in low-and middle-income countries seeking to strengthen community knowledge and skills in mental health. This case study uses a realist lens to explore how a mental health project in a context with few mental health services, strengthened community mental health competence by increasing community knowledge, creating safer social spaces and engaging partnerships for action. We used predominantly qualitative methods to explore relationships between context, interventions, mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Our rapid review returned 10 studies from nine countries across Asia (China, 5 India, [6][7][8] Malaysia, 9 Nepal 6, 10, 11 ), Africa (Ethiopia, 6,[11][12][13] Nigeria, 6,11 South Africa, 6 Uganda 6 ) and Europe (Lithuania 14 ). The majority of included studies were qualitative and conducted as part of a situation analysis, pilot study or other formative research.…”
Section: Figure 1: Flow Chart For Rapid Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Our rapid review returned 10 studies from nine countries across Asia (China, 5 India, [6][7][8] Malaysia, 9 Nepal 6, 10, 11 ), Africa (Ethiopia, 6,[11][12][13] Nigeria, 6,11 South Africa, 6 Uganda 6 ) and Europe (Lithuania 14 ). The majority of included studies were qualitative and conducted as part of a situation analysis, pilot study or other formative research.…”
Section: Figure 1: Flow Chart For Rapid Reviewmentioning
confidence: 99%
“…The majority of included studies were qualitative and conducted as part of a situation analysis, pilot study or other formative research. Three reported on user involvement in mental health policy and planning, 6,11,12 three on user involvement in mental health services or capacity-building of service providers, 5,7,10 and three on user involvement in treatment decisions. 9,13,14 Upon further consultation with the corresponding author, an additional study was identified as having involved users in data collection.…”
Section: Figure 1: Flow Chart For Rapid Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…These data highlight the central role of relationships in recovery and the imperative of building mutual understanding and supportive environments for families and households (Wyder & Bland, 2014;Foster et al, 2016;Price-Roberts et al, 2016). The evidence suggests that this support could be offered through individual and family-based counselling, peer support groups, self-help groups and advocacy group membership (Tew et al, 2012;Price-Robertson et al, 2016;Mathias et al, 2017).…”
Section: Family-centred Approachesmentioning
confidence: 99%